Effective typification of Ophrys apifera (Orchidaceae; Orchidoideae) - Ferrer-Gallego, P. Pablo (Phytotaxa, 2021)
Ophrys apifera Hudson was previously considered to have been lectotypified by Künkele and Baumann in 1998 with an illustration published by Matthias Lobel in 1581. However, Hudson did not include any references to Lobel in the protologue. Therefore, the typification by Künkele and Baumann is here briefly discussed and superseded because is being contrary to Art. 9.3 of the International code of nomenclature for algae, fungi, and plants (Shenzhen Code). The name is lectotypified here with an illustration published by Bauhin and Cherler in 1651. Unfortunately, this illustration does not show several diagnostic characters to distinguish O. apifera from other related species. Therefore, for a precise circumscription of the name, an epitype is proposed of a complete specimen preserved at K.